A New Approach to OTH Main Parameters Determination - Saavedra, Zenon (2019)
In this work, we propose a method based on a simulation that incorporates several models to provide the set of parameters needed on Over-The-Horizon radars (OTHR) performance evaluation, which consists in a versatile software tool. Obtaining the signals involved during transmission and reception is a complex and challenging task. Among them, the received signal is fundamental to design methods and algorithms in the target detection strategy. The parameters in the transmission and reception processes that define the radio link main features are determined in terms of target type, ionospheric conditions, radio link characteristics, and other environmental properties. The determination is done combining models to work assembled in a software tool that simulates the OTHR radio link. The tool gives the possibility of step away from the linear model, which uses mainly constant parameters and it is used commonly. A large number of set up parameters and also interconnections among several models enable to simulate nearer to actual search sceneries.